EVALUASI GEOMETRI JALAN ANGKUT DARI PIT KE DISPOSAL DI PT. AWOKGADING SARIRA NUSANTARA KABUPATEN LUWU TIMUR PROVINSI SULAWESI SELATAN - Jenius Nggata; Abdul Rauf (Retii, 2018)
The purpose of this research is to examine the condition of nickle hauling road and geometry calculation on PT. Awokgading Sarira Nusantara from mining pit to the disposal according to used Dump Truck Caterpillar 785C including straight road’s width, curve road’s width, radius of cumature, superelevation, road grade, and cross slope. It is also to be comparison based on AASHTO theory. Hauling operation played an important role. Safety and smoothly hauling operation never apart from both interaction hauling road and hauling equipments are selves. The actual condition of hauling road on straight road has 27 segments with wide size 28 – 31 m, whereas referenced on AASHTO theory calculation based on hauling equipment spesification, researcher got a result 23, 24 m. The curve road has 1 segment on STA 525 with actual width size 30,10 m, according to AASHTO minimum width for curve road is 25,98 m, radius of cumature size 14,38 m, and superelevation 1,3%. The actual grade from STA 01 – STA 28 is 0,42% – 9,85% with grade calculation is maximum 10%. Based on AASHTO theory, cross slope for straight road is 0,48 m and for curve road is 0,52 m.